Artistic manifestations of the borderline between tradition and modernity in Orhan Pamuk's novel "The Red-haired Woman" - Seyranyan, Lilit (Bulletin of Yerevan University B: Philology, 2022)
Orhan Pamuk's creative system is based on the problem of the possibility of dialogue between East and West, tradition and modernity. In the novel "The Red–haired Woman" are considered the development models typical of both the West – in the struggle between tradition and modernity, the modern wins (the image of Oedipus), and for the East - tradition wins in this struggle (the images of Rostam and Zohrab, Ivan the Terrible). In the novel, the young hero, because of jealousy of a red-haired woman and because of the desire for freedom, first leaves his "father" - a wounded master to die in a well, then dies himself by the hand of his son, brought up by the master – "grandfather". Thus, at first modernity defeats tradition, but tradition eventually "takes revenge" on modernity. The author of the novel emphasizes the possibility of a long hesitation of the next generations on this shaky border of tradition-modernity.In the ideological and aesthetic system of the novel, the artistic manifestations of this borderline are the following symbols and images: descending into the settlement of Ongeren and climbing up the mountain; cypresses between the heroes and the stars; cemetery; shining in the sky and shooting stars; well; eyes; owl, red color. The most important borderline image is a red-haired woman, which is based on the archetype of the mythical Lilith – a borderline being between Adam and Eve, God and the devil. It divides and unites the destinies of grandfather, master, father and son, i.e. generations. In the novel, the archetype of Lilith is contrasted with the archetype of Eve in the images of women devoted to the hearth and traditions – the mother and wife of the hero.Being red–haired is the heroine's choice. In the civilizational dimension, this woman symbolizes the Republic of Turkey, which is faced with a choice between East and West. A red-haired woman, as a borderline creature, can belong to several men: similarly, Turkey can be both East and West at the same time. The author of the novel has repeatedly spoken out about the problem of "fathers and sons", offering the following formula for its solution: based on the Ottoman tradition, open up to Europe. This is a natural position of Turkey, which throughout its history has appropriated the cultural traditions of other peoples, obtaining a eclectic identity.
Keywords: tradition; modernity; East; West; red-haired woman; Lilith archetype; borderline; development models